Can Impairment Interfere with Performance by Women with Carpal Tunnel Syndrome According to International Classification of Function? - Somayeh Kavousipor; Roya Mahmoodi; Marjan Jaladat; Ali Reza Ashraf (Shiraz University of Medical Sciences, 2015)
Background: Carpal tunnel syndrome is the most prevalent compression neuropathy of upper extremity which, two of the most important risk factors of that are the female sex and manual works. In the model of international classification of function, disability and health, disease is an impairment, results in functional limitation. The goal of this study is to compare hand function of participants between various severities of carpal tunnel syndrome. Methods: In a cross-sectional study, during 6 months period of time, 30 housekeeper women with carpal tunnel syndrome, with the mean age of 47.03 years, were selected through simple sampling. They were assessed for hand function, by Purdue peg board test and Boston questionnaire, after that a professional practitioner had performed Nerve Conductive Velocity (NCV) test and identified the severity of their diseases. Then the data were analyzed with SPSS software, by Kruskal-Wallis test. Results: The mean of Purdue peg board test and Boston questionnaire scores in various clusters of carpal tunnel syndrome severity, were not different (P>0.05). Conclusion: In this research, severity of electrodiagnostic findings of participants, with carpal tunnel syndrome, is not related to their performance and functional limitations.